Climate related sea-level variations over the past two millennia - Kemp, A. C.; Horton, B. P.; Donnelly, J. P.; Mann, M. E.; Vermeer, M.; Rahmstorf, S. (Proc Natl Acad Sci U S A, 2011)
We present new sea-level reconstructions for the past 2100 y based on salt-marsh sedimentary sequences from the US Atlantic coast. The data from North Carolina reveal four phases of persistent sea-level change after correction for glacial isostatic adjustment. Sea level was stable from at least BC 100 until AD 950. Sea level then increased for 400 y at a rate of 0.6 mm/y, followed by a further period of stable, or slightly falling, sea level that persisted until the late 19th century. Since then, sea level has risen at an average rate of 2.1 mm/y, representing the steepest century-scale increase of the past two millennia. This rate was initiated between AD 1865 and 1892. Using an extended semiempirical modeling approach, we show that these sea-level changes are consistent with global temperature for at least the past millennium.
id: 853; Kemp, Andrew C Horton, Benjamin P Donnelly, Jeffrey P Mann, Michael E Vermeer, Martin Rahmstorf, Stefan Proc Natl Acad Sci U S A. 2011 Jul 5;108(27):11017-22. Epub 2011 Jun 20.3131350submittedY